Symmetry operators and separation of variables in the (2+1)-dimensional Dirac equation with external electromagnetic field; International Journal of Geometric Methods in Modern Physics; Vol. 15, iss. 5 - Shapovalov A. V. Aleksandr Vasilyevich (2018, 2018)
Title screen